Effect of a 16-Week Combined Strength and Plyometric Training Program Followed by a Detraining Period on Athletic Performance in Pubertal Volleyball Players. Issue 8 (August 2019) - Fathi, Abed; Hammami, Raouf; Moran, Jason; Borji, Rihab; Sahli, Sonia; Rebai, Haithem
Abstract : Abstract: Fathi, A, Hammami, R, Moran, J, Borji, R, Sahli, S, and Rebai, H. Effect of a 16-week combined strength and plyometric training program followed by a detraining period on athletic performance in pubertal volleyball players. J Strength Cond Res 33(8): 2117–2127, 2019—The purpose of this study was to determine the effects of 16 weeks of combined strength and plyometric training or plyometric training alone and how a detraining program can modify adaptations in response to the training stimulus. Sixty male volleyball players (circa peak-height-velocity [PHV]: −1 to +1 year from PHV) were assigned to a combined training group (CTG) ( n = 20), a plyometric training group (PTG) ( n = 20), or a control group ( n = 20). The experimental groups (CTG and PTG) participated in training twice weekly for 16 weeks. Thigh muscle volume, body fat, flexibility, sprint, jump height, and medicine ball throw were measured before and after the intervention and after the period of detraining. Respectively, the CTG and PTG showed increases in thigh muscle volume (effect size: 0.71 and 0.42) and decreases in body fat (−0.42 and −0.34), as well as improvements in 5-m sprint (−0.69 and −0.46), 10-m sprint (−0.31 and −0.3), lower-body muscle power (0.44 and 0.36), and upper-body muscle power (1.32 and 0.7). After the detraining period, all groups maintained previously attained muscle power (6.79–9.87%; p < 0.001). In conclusion, combined strength and plyometric training provided better improvements than plyometric training only. The combination of strength and plyometric training is a time-effective training modality that confers improvements in physical performance measures, muscle size, and body fat. A temporary period of detraining may not undermine performance gains in pubertal volleyball players.